2023
DOI: 10.31234/osf.io/jvdpe
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

What Predicts AI Usage? Investigating the Main Drivers of AI Use Intention over Different Contexts

Abstract: Artificial Intelligence (AI) based applications are an ever-expanding field, with an increasing number of sectors deploying this technology. While previous research has focused on trust in AI applications or familiarity as predictors for AI usage, we aim to expand current research by investigating the influence of knowledge as well as AI risk and opportunity perception as possible predictors for AI usage. To this end, we conducted a study (N= 450, representative for age and gender) covering a broad number of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…As has been shown in several recent studies, risk and benefit perception are important predictors for AI usage (Potinteu et al, 2023, Schwesig et al, 2023. In the study of the authors identified risk and benefit perceptions as the most important predictor for use intention (with trust in AI only being second place).…”
Section: Risk and Benefit Perception Of Artificial Intelligencementioning
confidence: 93%
See 1 more Smart Citation
“…As has been shown in several recent studies, risk and benefit perception are important predictors for AI usage (Potinteu et al, 2023, Schwesig et al, 2023. In the study of the authors identified risk and benefit perceptions as the most important predictor for use intention (with trust in AI only being second place).…”
Section: Risk and Benefit Perception Of Artificial Intelligencementioning
confidence: 93%
“…While related research shows the benefit of causability concerning, for example, trust in AI (Druce et al, 2021;Glass et al, 2008;Larasati et al, 2021;Shin, 2021), we are, to our knowledge, the first to relate this concept to risk and benefit perception. Given the importance of risk and benefit perception regarding AI usage (Potinteu et al, 2023, Schwesig et al, 2023, increasing the perceived causability seems to be a promising method to decrease the risk and increase the benefit perception and, thus, increase the probability of AI usage in the medical sector. However, given that being in the high vs. low causability group did not result in any significant differences regarding risk and benefit perception further research in how to increase perceived causability is needed.…”
Section: Investigating the Relationship Between High Vs Low Causabili...mentioning
confidence: 99%